EXPLORATION OF INTERACTIVE LITERACY IN DEVELOPING STUDENTS' CRITICAL READING SKILLS: A SYSTEMATIC LITERATURE REVIEW (SLR) REVIEW - Nurhamidah, Didah; Mayuni, Ilza; Rasyid, Yumna (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This research aims to explore interactive literacy as a tool to develop critical reading skills. Interactive literacy, which includes the use of technology and digital media in the learning process, has become an important focus in higher education due to its ability to stimulate active engagement and critical thinking of students. Through the Systematic Literature Review (SLR) approach, this study reviewed relevant literature related to the application of literacy to improve critical reading skills. The process of searching and selecting articles is carried out by collecting research published in the last five years related to the application of literacy in various disciplines and educational contexts. The analysis was conducted on 150 articles that met the criteria for inclusion and relevance of the topic. The findings of this study show that literacy can improve students' critical reading skills by facilitating digital technology. In addition, literacy encourages students to be more active in exploring texts in depth and critiquing information more sharply, as well as developing the ability to connect new knowledge. Literacy has proven to be effective in improving critical reading skills, because it allows students to collaborate and discuss more openly, especially in improving critical reading skills that are needed in the academic and professional worlds. This study contributes to the development of more effective technology-based learning models in higher education environments. Keywords: interactive literacy, critical reading, systematic literature review